Preventing Foodborne Illness: Shigellosis - Keith R. Schneider; Soohyoun Ahn; Renée M. Goodrich-Schneider (EDIS)
Shigellosis occurs when virulent Shigella organisms are consumed and invade the intestinal mucosa, resulting in tissue destruction. Most Shigella infections are spread by stools or soiled fingers of an infected person to the mouth of another person when basic hygiene and handwashing are not properly done. This revised 5-page fact sheet was written by Keith R. Schneider, Soohyoun Ahn, and Renée M. Goodrich-Schneider, and published by the UF Department of Food Science and Human Nutrition, July 2012.